Cecal cancer with essential thrombocythemia treated by laparoscopic ileocecal resection: a case report - Masaya Hiyoshi; Hiroaki Nozawa; Kentaro Inada; Takayoshi Koseki; Keiichi Nasu; Yasuji Seyama; Ikuo Wada; Koji Murono; Shigenobu Emoto; Manabu Kaneko; Kazuhito Sasaki; Yasutaka Shuno; et al. (Surgical Case Reports)
Abstract Background Essential thrombocythemia (ET) is a myeloproliferative disorder characterized by thrombocytosis and a propensity for both thrombotic and hemorrhagic events. ET rarely occurs simultaneously with colorectal cancer. Here, we report a case of colorectal cancer in an ET patient treated using laparoscopic ileocecal resection. Case presentation A 40-year-old woman was admitted to our hospital after presenting with liver dysfunction. She had been previously diagnosed with ET; aspirin and anagrelide had been prescribed. Subsequent examination at our hospital revealed cecal cancer. Distant metastasis was absent; laparoscopic ileocecal resection was performed. Anagrelide was discontinued only on the surgery day. She was discharged on the seventh postoperative day without thrombosis or hemorrhage. However, when capecitabine and oxaliplatin were administered as adjuvant chemotherapy with continued anagrelide administration, she experienced hepatic dysfunction and thrombocytopenia; thus, anagrelide was discontinued. Five days later, her platelet count recovered. Subsequently, anagrelide and aspirin administration was resumed, without any adjuvant chemotherapy. Her liver function normalized gradually in 4 months. One-year post operation, she is well without tumor recurrence or new metastasis. Conclusions To our knowledge, this is the first report of laparoscopic colectomy performed on an ET patient receiving anagrelide. Our report shows that complications such as bleeding or thrombosis can be avoided by anagrelide administration. Contrastingly, thrombocytopenia due to anagrelide intake should be considered when chemotherapy that could cause bone marrow suppression is administered.